Preliminary Results of Extracorporeal Membrane Oxygenation Assisted Tracheal Sleeve Pneumonectomy for Cancer - Spaggiari, Lorenzo; Sedda, Giulia; Petrella, Francesco; Venturino, Marco; Rossi, Fabiana; Guarize, Juliana; Galetta, Domenico; Casiraghi, Monica; Iacono, Giorgio Lo; Bertolaccini, Luca; Alamanni, Francesco (The Thoracic and Cardiovascular Surgeon, 2020)
Objective Tracheal sleeve pneumonectomy is a challenge in lung cancer management and in achieving long-term oncological results. In November 2018, we started a prospective study on the role of extracorporeal membrane oxygenation (ECMO) in tracheal sleeve pneumonectomy. We aim to present our preliminary results.Methods From November 2018 to November 2019, six patients (three men and three women; median age: 61 years) were eligible for tracheal sleeve pneumonectomy for lung cancer employing the veno-venous ECMO during tracheobronchial anastomosis.Results Only in one patient, an intrapericardial pneumonectomy without ECMO support was performed, but cannulas were maintained during surgery. The median length of surgery was 201 minutes (range: 162–292 minutes), and the average duration of the apneic phase was 38 minutes (range: 31–45 minutes). No complications correlated to the positioning of the cannulas were recorded. There was only one major postoperative complication (hemothorax). At the time of follow-up, all patients were alive; one patient alive with bone metastasis was being treated with radiotherapy.Conclusion ECMO-assisted oncological surgery was rarely described, and its advantages include hemodynamic stability with low bleeding complications and a clean operating field. As suggested by our preliminary data, ECMO-assisted could be a useful alternative strategy in select lung cancer patients.
Keywords: extracorporeal membrane oxygenation; tracheal sleeve pneumonectomy; lung cancer